Competitive Strategies for Hospitals to Enhance Patient Loyalty at Mahkota Bidadari General Hospital in Langkat Regency, North Sumatra - Ramadani, Sri; Andriani, Rian; Mulyani, Kahar (Jurnal Indonesia Sosial Sains, 2026)
Competition between hospitals is currently increasing as the public's demand for fast, comfortable, and quality health services grows. In this situation, hospitals need to have a clear competitive strategy to be able to maintain patient trust and preferences. Patient loyalty is not only influenced by the results of treatment, but also by the overall service experience, such as the attitude of health workers, the availability of facilities, the timeliness of services, and the ease of the administrative process. The higher the patient loyalty, the higher the hospital's competitiveness, because patient loyalty creates a sustained competitive advantage through repeat visits, competency resilience, and positive recommendations. The purpose of this study was to analyze the application of cost leadership, differentiation, and focus strategies at RSU Mahkota Bidadari in order to increase patient loyalty. The research method used was descriptive with a qualitative approach, involving 4 resource persons from various hospital divisions such as the president director, service manager, doctor on duty and patients. RSU Mahkota Bidadari's competitiveness strategy in increasing patient loyalty is achieved through the integrated implementation of cost leadership, differentiation, and focus strategies by emphasizing standard-based service efficiency, humanistic and professional medical services, and consistency of service quality, thereby building patient trust, satisfaction, and loyalty in a sustainable manner. This research makes a theoretical contribution by expanding the understanding of the application of hospital competitiveness strategies in increasing patient loyalty, while integrating the concept of strategic management with health services.